2, 3, 17, 18‐Tetrahalohexaphyrins and the First Phlorin‐type Hexaphyrins. Issue 9 (18th June 2013) - Higashino, Tomohiro; Osuka, Atsuhiro
Abstract 1‐(Triisopropylsilyl)‐3, 4‐dichloropyrrole and 1‐(triisopropylsilyl)‐3, 4‐difluoropyrrole were conveniently prepared from the corresponding 3, 4‐dibromopyrrole by lithiation followed by halogenation. 2, 3, 17, 18‐Tetrahalogeno [26]‐ and [28]hexaphyrins have been prepared by condensation of 3, 4‐dihalopyrroles and a dipyrromethane‐dicarbinol. 2, 3, 17, 18‐Tetrahalogenated hexaphyrins display variable structural and electronic properties depending upon the halogen atom and the number of π‐electrons. Tetrabromo[28]hexaphyrin and tetrachloro[28]hexaphyrin were further reduced with excess NaBH4 to furnish meso‐reduced hexaphyrins as the first example of phlorin‐type meso‐aryl‐substituted hexaphyrins.